2015
DOI: 10.1111/jgs.13834
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐Effectiveness of a Chronic Care Model for Frail Older Adults in Primary Care: Economic Evaluation Alongside a Stepped‐Wedge Cluster‐Randomized Trial

Abstract: Because the GCM was not cost-effective compared to usual care after 24 months of follow-up, widespread implementation in its current form is not recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
4
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(77 citation statements)
references
References 44 publications
5
67
4
1
Order By: Relevance
“…[19] Recent studies in the Netherlands and Finland which were performed from a societal perspective, found no evidence for the cost-effectiveness of multifactorial preventive interventions in preventing or postponing new disabilities as compared with usual care. [1316, 48] This is consistent with the results of our study. Two other recent studies which were performed from a societal perspective, found that their intervention was cost-effective at high willingness to pay ratios (EUR 20,000 and 50,000 Australian dollars (= EUR 32,327) respectively).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…[19] Recent studies in the Netherlands and Finland which were performed from a societal perspective, found no evidence for the cost-effectiveness of multifactorial preventive interventions in preventing or postponing new disabilities as compared with usual care. [1316, 48] This is consistent with the results of our study. Two other recent studies which were performed from a societal perspective, found that their intervention was cost-effective at high willingness to pay ratios (EUR 20,000 and 50,000 Australian dollars (= EUR 32,327) respectively).…”
Section: Discussionsupporting
confidence: 93%
“…A large variety consists between the total cost per participant over a one-year period between different studies in the intervention group (the estimated total amounts vary between EUR 13,251 and EUR 19,353). [15, 48] The total cost per participant described in our study are substantially lower than the total costs described in these other studies. This may have resulted from the exclusion of informal care cost in our study.…”
Section: Discussioncontrasting
confidence: 67%
“…No effects were found on "hard" outcomes, such as hospital admissions No effects on quality of life (SF-12), health-related quality of life, functional limitations, self-rated health, psychological well-being, social functioning and hospitalisations [10]. The intervention is not costeffective [13].…”
Section: Results From Three Recent Studies In the Netherlandsmentioning
confidence: 99%
“…It should be noted that both the ACT trial and the U-PROFIT trial found a small effect of the intervention on functional limitations (IADL or a combined ADL/IADL measure), but the effects were not statistically significant after correction for multiple comparisons (ACT) [10], or the effect size was very small and not clinically relevant (U-PROFIT) [12]. The interventions of the ACT trial and the PoC trial were not cost-effective compared with usual care [13,14]. The intervention of the U-PROFIT trial had a small likelihood of being cost-effective, but only with large willingness to pay values.…”
Section: E O Hoogendijkmentioning
confidence: 99%
“…However, so far the evidence on the effectiveness of integrated care for people with geriatric conditions has been mixed. While some interventions were found to have contributed to a reduction in symptoms, emergency department visits, acute hospital admissions and hospital bed days [19, 20], other interventions showed no improvements in length of hospital stay, use of care, prevention of adverse outcomes, health status and costs [2025]. In addition to this heterogeneity in outcomes, there was also a considerable variation in the interventions themselves, which ranged from telehealth education, discharge planning and community support, and multidisciplinary pathways to integration of acute, chronic and social care.…”
Section: Introductionmentioning
confidence: 99%